APLIKASI PEMBELAJARAN SEJARAH PAHLAWAN INDONESIA DI WILAYAH SUMATERA (STUDI KASUS SDN 2 SUMBEREJO) - Zacky Musthofa (Journal of Engineering, Computer Science and Information Technology (JECSIT), 2022)
Learning systems that are still conventional make students easily feel bored and bored in learning because the learning system is monotonous. Many teachers experience difficulties in educating their students to be able to understand and understand the material being explained. The benefit of this research is to increase students' interest in learning and make it easier for teachers to teach. As well as reminding and informing the public of the services of Indonesian Heroes. At the same time encouraging innovation and creativity from teachers in teaching the values of the history of Indonesian heroes that are conducive to students, by adding learning media interactive learning media. Applications can be continued because the application is feasible with a total calculation of 100% of application eligibility. Testing this application was carried out as many as 11 test actions. Where there are no error messages or function errors being tested.